2017
DOI: 10.1038/npp.2017.176
|View full text |Cite
|
Sign up to set email alerts
|

Rodent Mismatch Negativity/theta Neuro-Oscillatory Response as a Translational Neurophysiological Biomarker for N-Methyl-D-Aspartate Receptor-Based New Treatment Development in Schizophrenia

Abstract: Deficits in the generation of auditory mismatch negativity (MMN) generation are among the most widely replicated neurophysiological abnormalities in schizophrenia and are linked to underlying dysfunction of N-methyl-D-aspartate receptor (NMDAR)-mediated neurotransmission. Here, we evaluate physiological properties of rodent MMN, along with sensitivity to NMDAR agonist and antagonist treatments, relative to known patterns of dysfunction in schizophrenia. Epidural neurophysiological responses to frequency and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 61 publications
4
33
0
Order By: Relevance
“…In humans, N1 responses map primarily to the theta frequency range, and thus may interrelate with circuit motifs involving non-PV interneurons, especially SOMs (Javitt et al, submitted). Our finding of significant aERP response in mice following NMDAR blockade is consistent with prior studies in monkey (Javitt et al, 2000) and rodent (Bickel et al, 2008;Connolly et al, 2004;Lee et al, 2018;Maxwell et al, 2006). The lack of effect of SRKO on the rodent N1 response may thus suggest that the model recapitulates the PV-related aspects of NMDAR dysfunction in Sz more fully than it captures dysfunction of other neuronal populations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In humans, N1 responses map primarily to the theta frequency range, and thus may interrelate with circuit motifs involving non-PV interneurons, especially SOMs (Javitt et al, submitted). Our finding of significant aERP response in mice following NMDAR blockade is consistent with prior studies in monkey (Javitt et al, 2000) and rodent (Bickel et al, 2008;Connolly et al, 2004;Lee et al, 2018;Maxwell et al, 2006). The lack of effect of SRKO on the rodent N1 response may thus suggest that the model recapitulates the PV-related aspects of NMDAR dysfunction in Sz more fully than it captures dysfunction of other neuronal populations.…”
Section: Discussionsupporting
confidence: 92%
“…Like ASSR, deficits in auditory N1/P2 response have been extensively documented in Sz (Ford et al, 2001;Javitt et al, 2008;Shelley et al, 1999;Turetsky et al, 2009). Also like ASSR, Sz-like deficits in auditory N1 generation are induced by NMDAR antagonists in both monkey (Javitt et al, 2000) and rodent (Connolly et al, 2004;Lee et al, 2018;Maxwell et al, 2006;Schuelert et al, 2018) models. However, as opposed to ASSR, power associated with the auditory N1/P2 component maps predominantly to the theta frequency range, implicating somatostatin (SOM) interneuron related circuits Javitt and Sweet, 2015;Womelsdorf et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The MMN is a theta-dominant response with separable frontal and temporal processes (Fuentemilla, Marco-Pallarés, Münte, & Grau, 2008;Ko et al, 2012) that may interact with theta-band phase synchrony (Choi et al, 2013). The neural systems underlying auditory novelty detection are well detailed in rodent models (Escera & Malmierca, 2014;Featherstone, Melnychenko, & Siegel, 2018;Lee et al, 2018), facilitating further cross-species translation. Auditory evoked responses are already routinely used in brainstem auditory testing for hearing acuity in newborns, again demonstrating that clinical infrastructure and expertise exists for applying relevant tasks to patient groups when using EEG as a diagnostic tool.…”
Section: Mechanisms To Biomarkersmentioning
confidence: 99%
“…Therefore, MMN research in nonhuman animals can help reveal the neural mechanisms of MMN generation and its deficits . Currently, the few studies observing MMN evoked by duration deviance in rats have produced inconsistent results in the response latency window and polarity of MMN . Acoustic stimuli used in these studies (1‐ to 4‐kHz tones) were located at the lower end of the hearing range in rats; therefore, it was possible that the frequency of these sound stimuli was not suitable for MMN induction.…”
Section: Introductionmentioning
confidence: 99%
“…13 Currently, the few studies observing MMN evoked by duration deviance in rats have produced inconsistent results in the response latency window and polarity of MMN. [14][15][16][17] Acoustic stimuli used in these studies (1-to 4-kHz tones) were located at the lower end of the hearing range in rats 18 ; therefore, it was possible that the frequency of these sound stimuli was not suitable for MMN induction. Notably, a recent study using 7-to 18-kHz sound stimuli observed large MMN-like potentials to pitch changes.…”
mentioning
confidence: 99%